(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Pulmonary tuberculosis (PTB) remains a major public health problem especially in the developing countries. Literature evidence opines that serological markers associated with PTB infections enhance early diagnosis. This study employed CD4+ T-lymphocyte counts and total serum immunoglobulin to establish early diagnosis in PTB patients in Uyo. Sputum samples of 105 patients were screened for Acid Fast Bacilli, while blood (7ml) was collected for CD4+ T-lymphocyte counts and quantification of total serum using cytoflow counter and Enzyme linked Immunoassay, respectively. A prevalence of 12.4% was established for PTB infection among the patients. The mean differences between immunoglobulins levels in relation to CD4+ T-lymphocyte counts was not significant at p ˃ 0.05. The mean IgG value of PTB patients was 737.29 ± 435.8 mg/dL, while the apparently healthy subjects (AHS) had the mean IgG value of 23.15 ± 32.2 mg/dL. The mean IgA level in PTB patients (190.91 ± 94.8 mg/dL) was higher than that of AHS (126.81 ± 35.5 mg/dL). The mean IgM value of PTB patients and that of the AHS was 317.75 ± 146.11 and 50.00 ± 32.3 mg/dL, respectively. There was significant difference between the immunoglobulin levels of PTB patients and AHS at p > 0.05 with respect to IgA and at p > 0.001 with respect to IgG and IgM. This study has indicated that biomarkers of humoral immunity were significantly affected when compared with AHS, thus, this study would enhance knowledge of the health practitioners and enable them to grasp the role of biomarkers in